A Implantação de unidades de conservação e o direito da pessoa humana ao meio ambiente equilibrado - Sugahara, Juliana Wayss (2014)
The right to a balanced environment, enshrined in CF88, is considered a fundamental right, in that it harnesses the dignity of the human person in order to protect the healthy quality of life of the human person. Although not conceptualise the environment, the CF88 (art. 225) gives the expression a comprehensive and systemic view, involving ecological, social, economic, spatial, cultural and political factors. Thus, the realization of this fundamental right presupposes Sustainable Development, adopted as a model for national development and condition for the exercise of human dignity. In this sense, derives from the right to a balanced environment a set of state and social duties of ensuring the quality of life, in a systemic perspective. Thus, the State has mechanisms and instruments that enable the promotion and execution of actions that search, among them, the establishment of protected areas (PAs), established in accordance with the methods and legal criteria of National System of Units Conservation of Nature (SNUG), to be mandatorily followed by the Government. As a system, the SNUG aims, ultimately, to safeguard the environment, therefore, set out to regulate article 225, § 1, sections I, II, III and VII of CF88. However, it is commonly observed that the deployment of PAs, the natural factor (or ecological) prevails over the others. Thus, the research assumed that the deployment of PAs not adopt systemic constitutional model of sustainability, prevailing natural variable, which violates the fundamental human right to a balanced environment, which presupposes Sustainable Development. Through a holistic, interdisciplinary approach, the research aimed to examine whether the implementation of state protected areas in northeastern Brazil is effectively serving the purpose of ensuring the human right to a balanced environment. The study demonstrated dysregulation between legislation and environmental policy effectively held by public administration, so that the systemic constitutional model of sustainability is not adopted. The inefficiency of policy protection assumed does not follow the law, but the absence of coordinated actions in search of Sustainable Development.